Learning to teach in an age of accountability - Costigan, Arthur T. (L. Erlbaum Associates, 2004)
This work documents the "brave new world" of teacher, administrator, school, and student accountability that has swept across the US in recent years. Its particular vantage point is the perspective of dozens of new teachers trying to make their way through their first months and years working in schools in the New York City metropolitan area.